Expanding the structural analysis capabilities on an Orbitrap-based mass spectrometer for large macromolecular complexes. Issue 1 (15th November 2017) - Fort, Kyle L.; van de Waterbeemd, Michiel; Boll, Dmitriy; Reinhardt-Szyba, Maria; Belov, Mikhail E.; Sasaki, Eita; Zschoche, Reinhard; Hilvert, Donald; Makarov, Alexander A.; Heck, Albert J. R.
Abstract : Native mass spectrometry can provide insight into the structure of macromolecular biological systems. Abstract : Native mass spectrometry can provide insight into the structure of macromolecular biological systems. As analytes under investigation get larger and more complex, instrument capabilities need to be advanced. Herein, modifications to an Orbitrap Q Exactive Plus mass spectrometer that increase signal intensity, mass resolution, and maximum m / z measurable are described.